Tejiendo Redes : El VIH Visto a Través de 14 Activistas de Latinoamérica. - Báez, Frank (Consejo Latinoamericano de Ciencias Sociales, 2021)
Weaving networks: HIV seen through 14 Latin American activists is a collective book, a carousel of anecdotes, stories, opinions and analysis about one of the great pandemics of our time: AIDS. Forty years after the first clinical description of cases of what was known as the Acquired Immunodeficiency Syndrome, we find ourselves at a propitious moment to see the phenomenon of this pandemic with greater perspective. Definitely, the situation is ideal to discuss the issue of HIV and who better than the activists of our region to tell us about the desperation and ostracism suffered. But also, so that they tell us how, despite the stigmas and limitations, they managed to find solutions, get together, organize and create a better future for the new generations.